DIMENSI PARTISI PADA GRAF GRID - Haspika Haspika; Hasmawati Hasmawati; Naimah Aris (Department of Mathematics, Hasanuddin University, 2023)
Graph G is a discrete set pair with the notation V(G) with its element called a vertex and the set of different and unordered pairs with the notation E(G) where the element is called edge. One type of graph Gm,n is a grid graph that is notated is a graph of the result of the operation between two path graphs (Pm*Pn). The set of partition∏ =S1,S2,…,Sk of V(G) is called a resolving partition if its representation for each vertex on graph G is different. The cardinality of the minimum resolving partition of graph G is the partition dimension of the graph G denoted pd(G). This paper discusses the dimension of the grid graph partition Gm,n with the result pd(Gm,n) = 3 for m,n>=2 with n even value.